Physiotherapy Management for Cases of Tendinitis Bicipitalis in Indonesian Para Powerlifting Athletes: Case Report - Heru Purnomo; Suryo Saputra Perdana; Amalia Nur Azizah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Bicipitalis tendinitis is an inflammation of the biceps tendon, which is the connective tissue between the biceps muscle and the humerus bone. This inflammation can cause pain, swelling and limited movement. The prevalence of bicipital tendinitis in Indonesia in 2023 is estimated at 2.5% of the general population. the prevalence of bicipital tendinitis in adults aged 18-65 years is 2.5% that athletes who use the bicep muscle more often, such as weightlifters, have a higher risk of suffering from bicipital tendinitis. If left untreated, it will hamper exercise and daily activities.The sample in this study amounted to 1 client. Data collection methods by means of subjective examination, objective examination, motion examination, examination of cognitive abilities, personal and interpersonal skills, functional examination and activity environment, and specific examination. This type of descriptive case study research uses participatory observation methods, physiotherapy intervention procedures with Ultrasound, TENS and Hold Relax exercise. The subject in this study was An. Sh is a 33 year old para-powerlifting athlete by profession, the patient is 177 cm tall and weighs 70 kg. The patient came to the NPC Indonesia physiotherapy clinic on August 25, 2023 because the patient complained of pain in the right front shoulder. muscle examination obtained normal results in all physical examinations except for the pain examination performed with Visual Analoque Scale (VAS) obtained silent pain 2/10, tenderness 5/10 and motion pain 6/10. The physiotherapist conducted a specific examination obtained positive Yergason Test results and a positive Speeds Test indicating the occurrence of dextra Bicipitalis Tendinitis. The results after being given intervention in Bicipitalis Tendinitis patients with Ultrasound, TENS and Hold Relax exercise for 6 times therapy in 2 weeks are a significant decrease in pain and an increase in activity.